Brides and doom : gender, property, and power in medieval German women's epic - Frakes, Jerold C. (Philadelphia : University of Pennsylvania Press, 1994)
Jerold C. Frakes approaches the Nibelungenlied, the Klage, and the Kudrun, epic poems central to the Middle High German tradition, through a set of literary, economic, ad sociological interpretations, informed by a broad range of contemporary feminist scholarship.
Frontmatter -- Contents -- 1. Introduction -- 2. Philology and/as Patriarchy: The Conventions of Nibelungenlied Scholarship -- 3. Women, Property, and Power -- 4. Pillow Talk: Intimate Conversations -- Political Strategies -- 5. Teuton as Amazon: The Devil's Bride and the She-Devil -- 6. Inconclusive Intermezzo: The Monsters, the Critics, Diu Klage -- 7. Women, Sovereignty, and Class in Kudrun -- 8. Suone as Social (Trans)formation -- 9. Women's Epic and/as Masculist Backlash -- Bibliography -- Index
Includes bibliographical references (pages 267-287) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Epic poetry, German -- History and criticism; German poetry -- Middle High German, 1050-1500 -- History and criticism; Women -- Germany -- History -- Middle Ages, 500-1500.; Feminism and literature -- Germany -- History; Women and literature -- Germany -- History; Civilization, Medieval, in literature; Power (Social sciences) in literature; Sex role in literature; Property in literature; Poésie allemande -- 1050-1500 (Moyen haut allemand) -- Histoire et critique; Femmes -- Allemagne -- Histoire -- 500-1500 (Moyen Âge); Femmes et littérature -- Allemagne -- Histoire; Civilisation médiévale dans la littérature.; Pouvoir (Sciences sociales) dans la littérature.; Rôle selon le sexe dans la littérature.; Poésie épique allemande -- Histoire et critique; POETRY -- Continental European; LITERARY COLLECTIONS -- Medieval; Civilization, Medieval, in literature; Epic poetry, German; Feminism and literature; German poetry -- Middle High German; Power (Social sciences) in literature; Property in literature; Sex role in literature; Women and literature; Women -- Middle Ages; Germany; 500-1500; Criticism, interpretation, etc; History